2016
DOI: 10.1021/acs.langmuir.6b00077
|View full text |Cite
|
Sign up to set email alerts
|

Role of Side Chains in β-Sheet Self-Assembly into Peptide Fibrils. IR and VCD Spectroscopic Studies of Glutamic Acid-Containing Peptides

Abstract: Poly(glutamic acid) at low pH self-assembles after incubation at higher temperature into fibrils composed of antiparallel sheets that are stacked in a β2-type structure whose amide carbonyls have bifurcated H-bonds involving the side chains from the next sheet. Oligomers of Glu can also form such structures, and isotope labeling has provided insight into their out-of-register antiparallel structure [ Biomacromolecules 2013 , 14 , 3880 - 3891 ]. In this paper we report IR and VCD spectra and transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…types 1 to 4 ) and local chromophore structure ( F or T ). This is consistent with previous VCD fibril measurements revealing a remarkable variability of spectral shapes with respect to studied systems . However, the theoretical g ‐factors seem to be quite small compared to maximal values observed experimentally (~10 −2 ‐10 −3 , e.g., Figure ).…”
Section: Resultssupporting
confidence: 91%
“…types 1 to 4 ) and local chromophore structure ( F or T ). This is consistent with previous VCD fibril measurements revealing a remarkable variability of spectral shapes with respect to studied systems . However, the theoretical g ‐factors seem to be quite small compared to maximal values observed experimentally (~10 −2 ‐10 −3 , e.g., Figure ).…”
Section: Resultssupporting
confidence: 91%
“…Dotted lines are guides for the eyes indicating the positions of main peaks appearing in the spectra. The mode at 1600 cm −1 , associated to β 2 ‐sheets, is highlighted in bold…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, Glu ‐ rich peptides have gained more attention mainly due to the ability of carboxylic side chains to form certain types of H‐bond networks . Particularly, it has been demonstrated that Glu‐enriched sequences stack into antiparallel sheets, forming β 2 ‐type structures held together by bifurcated H bonds between amide carbonyls and carboxylic acid side chains in neighboring sheets . These structural insights have been derived mainly from Fourier transform infrared (FTIR) absorption and circular and vibrational circular dichroism (CD and VCD) .…”
Section: Introductionmentioning
confidence: 99%
“…One check is to rotate the sample about the optical axis to test for orientation sensitivity. In particular, enhanced VCD of fibrillar samples have been shown to be diagnostically useful, although the origin of the enhancement is still not fully clear . While it is desirable to express VCD in molar units, eg, ε and Δε, for analyses by theoretical modeling, IR‐based biomolecular experiments tend to be inaccurate for both concentration and path lengths, making these values unreliable.…”
Section: Methodsmentioning
confidence: 99%